Paraphalaenopsis laycockii (M. R. Henderson) A. D. Hawkes: TINJAUAN TERHADAP MORFOLOGI TANAMAN DAN ANATOMI DAUN - Yulia, Nina Dwi; Juliarni, Juliarni (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2007)
Porophaloenopsis laycockii is an epiphytic orchid, endemic to Borneo. The orchid is not widely known since this orchid is rare and the trade of this species is restricted by the law. An observation was made to provide information on plant morphology and leaf anatomy of the species. Among various characters recorded, it was noted that the pencil-or-rat-tail-like leaf is about 5.66 mm in diameter and up to 1 m in length. It has relatively large stomata measuring 66.8 x 57.3 pm with low stomata density of 16.3 stomata per mmÂ° of leaf surface area. These characters may influence its water management so that the plant should be grown and maintained in shade for better establishment.